Escrita, paisagem e saúde na literatura indígena - Rafael Otávio Fares Ferreira (2017)
From the intercultural and transdisciplinary experience of producing three indigenous books on health, Curar (Hitupmana'a), The Maxakali Book tells a story about the forest (Tikm'n Mxakani 'yõg mmati'ãgtux yõg tappet), both written by the Maxakali and The Living Book (Una Hiwea), made by the Huni Ku, this work seeks to delineate the concept of landscape in indigenous textualities. By undoing dichotomies such as myth and science, primitive and civilized, words and things, in a relationship not of representation but of interaction, the landscape implies symbiotically in the writings, in the knowings and in the proper forms of indigenous knowledge. Thus, it also permeates the conceptions of disease and cure, that is, what these people consider health. The proposal that these books point us is a great health, beyond human: the healing of the earth. A cure that needs to handle the writing for thecultivation of landscapes that thought allows and that the planet needs to survive. For this task, we use the Perspectivism theory of the Anthropologist Eduardo Viveiros de Castro, the formulations on the writing of Maria Gabriela Llansol and the concept of becoming of Gilles Deleuze and Félix Gattari.